An exploratory public health investigation of the correlation between food allergies and pediatric obesity (Annals of Medical Research, 2021)
Aim: The study compared Skin Prick Test results in different age groups and different Body Mass Index categories, in order to investigate a possible association between allergies and pediatric obesity. Materials and Methods: Forty-four 4-16 year-old children, who were referred to Istanbul Kagithane State Hospital with allergies and at least one positive test result, were retrospectively evaluated in cross-sectional analysis of ecological design.Results: Children with walnut allergies had a higher Body Mass Index mean value. Twenty-eight children with walnut allergies had a BMI mean of 25.96 and sixteen children without walnut allergies had a BMI mean of 21.97. It has been suggested that Skin Prick Test is an easy method to apply in identifying allergies. The study revealed a significant difference for BMIs only in cases with walnut allergies. Mean ages of children with chicken, cocoa, white flour allergies were high. Mean age of children with chicken meat, white flour, cocoa allergies differed significantly. Conclusion: Current research suggests that careful consideration should be given to nutritional awareness and the adoption of informed dietary practices in childhood.
Keywords: Allergy; BMI; children; teenager; public health